THE IMPACT OF STRUCTURED MOTOR SKILL INTERVENTIONS ON MANIPULATIVE SKILLS IN EARLY CHILDHOOD - Shivaraju K; R. Ramakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examined the effects of a 12-week structured motor skill intervention on manipulative skills in 6- to 7-year-old boys from a public school in Bengaluru, India. Sixty participants were randomly assigned to either an intervention group (n = 30) receiving thrice-weekly, 45-minute skill-focused sessions or a control group (n = 30) continuing standard physical education. The Test of Gross Motor Development-2 (TGMD-2) assessed six manipulative skills at baseline and after-intervention. Results revealed significant improvements in the intervention group, while the control group showed no meaningful change. ANCOVA confirmed superior post-test performance in the intervention group after controlling for baseline scores. The results show that organized, regular motor skill interventions can greatly improve the manipulative skills of young primary school children compared to regular physical education. The data show that targeted motor programs should be used in early childhood education to help kids learn basic movement skills. This could have long-term benefits for their physical activity levels.